Implementasi Fungsi Manajemen Dakwah dalam Pelaksanaan Program Menghafal Al-Qur’an di SDIT Islamiyah Proyek Desa Belinteng - Irma Yunisa; Faridah Faridah (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
This study looks at how da'wah management plays a role in running the Qur'an memorization curriculum at SDIT Islamiyah Proyek Desa Belinteng. The tahfizh program isn't just seen as a way to pass on religious knowledge it's also viewed as a da'wah tool and a means of building religious character in students from an early age. The study aims to explore how management functions including planning, organizing, directing, and evaluating are applied in running the tahfizh program at the school. The research uses a descriptive qualitative approach, with data collected through interviews, observation, and document review. The key informants were the school principal and the tahfizh teachers. The findings show that the tahfizh program has been managed in a fairly structured way, covering memorization target-setting, clear division of responsibilities, regular memorization sessions, and periodic progress assessments. Beyond improving students' memorization skills, the program also helps instill discipline, good manners, and a love for the Qur'an. That said, the program still faces some challenges, mainly students' lack of focus and limited muroja'ah practice at home.